OPTIMALISASI BUKAAN DAN KENYAMANAN RUANG MELALUI ANALISIS OTTV DAN SUN SHADING - Wibawa, Baju Arie; Hutama, Alif Nur (MODUL, 2019)
The window as the opening of natural lighting is more critical to conserve building energy, but if the size opening is too broad will increase the solar heat into the room. Over of heat, will also cause discomfort in the place because the value of OTTV (overall thermal transfer value) will also increase. The purpose of this study is to identify components, calculate the OTTV value and the analysis of shadow of the sun into the room. In the meeting room of the UPGRIS post-graduate building, there is too many windows that make the room glare and hot. It is felt to affect inefficient artificial energy (Air Conditioning). The method used is a type of quantitative research with an experimental approach. The results of the OTTV study in this room is 52.33 watts/m2, and this is exceeded from SNI (35 watts/m2). This research redesign of windows and shading to comply with maximum standard.